Experimental setting and protocol impact human colour preference assessment under multiple white light sources - Deng, Xue; Liu, Yixuan; Tian, Baolin; Zhang, Wei; Yu, Feng; Liu, Qiang (Frontiers in Neuroscience, 2022)
Psychophysical experiment is the most straightforward and reliable way to investigate the impact of lighting on visual colour perception. In this study, a series of experiments were conducted in order to investigate the impact of experimental setting and protocol on the obtained conclusions in visual tests regarding human preference on object colour in applied lighting research. Four light sources of 5,500 K, with Duv values of −0.01, 0, 0.015, and 0.02, were used to illuminate different kinds of objects including blue jeans, fruit and vegetables, bread, artware, fresh pork, and skin tones. The use of those experimental light sources and objects was to provide control study for our former research by deliberately changing certain experimental setup and protocol and testify the robustness of our former conclusions. The results show that some of our former findings, like the dominant impact of lighting on colour preference, the visual cognition process of light booth experiments as well as the correlation between the whiteness of lighting and colour preference, were found to be valid in typical light booth experiment. The impact of experimental object turned out to be much stronger under the newly designed protocol and the significance of sex difference on colour preference judgment was found to vary with experimental setup. These new findings highlight the influence of experimental setting and protocol on the validity of research findings, which we believe, could provide deeper understanding for the psychophysical results of current colour preference studies.